Research note: In vitro anticoccidial activity of protein and lipid extracts from the black soldier fly larvae (Hermetia illucens) - Laura Sedano; Maryline Abert Vian; Côme Guidou; Francoise I. Bussière; Sonia Lacroix-Lamandé; Christophe Trespeuch; Bertrand Méda; Anne Silvestre (Poultry Science)
Avian coccidiosis, caused by Eimeria spp., is the main parasitic disease in the poultry industry, responsible for high economic costs worldwide. Faced with anticoccidial resistance and societal pressure to reduce inputs in livestock sector, insects could provide a relevant alternative to anticoccidial molecules. The larvae of the black soldier fly (Hermetia illucens) are easy to rear, and can be used to enhance the value of by-products and food waste. Here, anticoccidial activities of protein extracts solubilized in water and lipid extracts solubilized in methanol of H. illucens larvae were evaluated in vitro. Larvae were either blanched and freeze-dried or dried and pressed. The maximum noncytotoxic dose of each extract (20 g/L and 35 g/L of dry matter equivalent) was assessed in avian cells, using a series of tenfold dilutions. The parasite strain Et-INRAE was modified to express nano-luciferase reporter gene. Parasites were pre-treated with extracts. Then, avian cells were infected and incubated in the presence of the extracts. Inhibition of cell invasion and parasite development were assessed by quantification of the luminescence detected. Lipid extracts and protein extracts inhibit Eimeria growth at, at least, a 10⁻⁶ dilution. Further research is required to confirm these results in vivo, assess potential antinutritional effects, and possibly identify active compounds from fractionated extracts to optimize the observed anticoccidial activities.